1994
DOI: 10.2105/ajph.84.4.606
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adolescent work injuries reported to the Minnesota Department of Labor and Industry.

Abstract: OBJECTIVES. The purpose of the study was to provide descriptive data and incidence data on adolescent work-related injuries and to determine whether such injuries are underreported to the Minnesota Department of Labor and Industry. METHODS. The study consisted of a 1-year survey of 534 adolescent work-related injuries reported to the Department of Labor and Industry and a cross-sectional survey of 3312 public high school students from throughout Minnesota. The high school survey used an abbreviated questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 9 publications
1
66
1
3
Order By: Relevance
“…Self-reported measures have been effectively used in workplace accident analyses and safety surveys (e.g., Gyekye and Salminen [15,61] and Siu et al [34]). Besides, while epidemiologic reports were found to be faulty, biased and deficient because of poor documentation [62,63], research reports have found self-reported accident rates to be closely related to documented accident rates [64]. Notwithstanding these limitations, the current study contributes to the growing body of research, which has identified work experience as an important variable for investigation in safety management policies.…”
Section: Safety Implications and Directions For Further Studiesmentioning
confidence: 81%
“…Self-reported measures have been effectively used in workplace accident analyses and safety surveys (e.g., Gyekye and Salminen [15,61] and Siu et al [34]). Besides, while epidemiologic reports were found to be faulty, biased and deficient because of poor documentation [62,63], research reports have found self-reported accident rates to be closely related to documented accident rates [64]. Notwithstanding these limitations, the current study contributes to the growing body of research, which has identified work experience as an important variable for investigation in safety management policies.…”
Section: Safety Implications and Directions For Further Studiesmentioning
confidence: 81%
“…Selfreported measures have been effectively used in accident and safety analyses (e.g., Gyekye, 2005Gyekye, , 2006Siu et al, 2003). Besides, while epidemiologic reports have been found to be faulty, biased and deficient because of poor documentation (Parker et al, 1994;Veazie et al, 1994), research reports have found self-reported accident rates to be closely related to documented accident rates (Smith et al, 2001). Notwithstanding the above-mentioned limitation, the current study contributes to the growing body of research which has identified educational status as important variable for investigation in safety management policies.…”
Section: Safety Implications and Directions For Further Studiesmentioning
confidence: 99%
“…Reporting also varies between counties and groups of workers, e.g. workers in sparsely populated areas, women, young people, and those who are selfemployed and precariously employed (Parker, Carl, French & Martin, 1994;Quinlan & Mayhew, 1999). However, a study of hospital environmental service workers found underreporting more likely among older workers and those having worked longer time at the same job (Weddle, 1996).…”
Section: Reporting Occupational Disordersmentioning
confidence: 99%